(untitled) (London Journal of Medical and Health Research, 2024)
Objective: Get to know and mark the perception of nursing students about the subject and about the factors that influence their power on the subject. Methodology: A descriptive study with a qualitative approach was carried out. Elected 19 students of the Nursing Bachelor’s degree enrolled at the Centro Universitário Euro Americano (UNIEURO), data collection took place through interviews with semi-structured scripts.